Schaum's outline of theory and problems of strength of materials - Nash, William A (Schaum's outline series., 1994)
This edition contains 12 computer programs and treats stress concentrations and fracture mechanics. It also includes 345 solved problems. New problems to this edition stem from contemporary applications in a variety of engineering areas, including civil, mechanical, aeronautical and ocean, as well as medical application. The work also contains material on energy methods and unsymmetric binding of beams.